SIBERNETIK DAN TEORI KONSTRUKTIVIS DALAM PENGAJARAN - Asnawi, Asnawi (Jurnal Mentari, 2010)
A teacher should know a lot of theories that can be applied in teaching and learning process either English or other subjects. The current theories nowadays used by teachers are behaviorist theory, nativist approaches, computer-supported collaborative learning (CSCL) theories, cybernetics and constructivism theories. The focus of this article is to elaborate cybernetics and constructivism theories. The aim of this article is to briefly describe the cybernetics and constructivism theories in teaching and learning which covers the definition of cybernetics and constructivism, principles of constructivism learning, the characteristics of constructivism learning and teaching, the role of teachers and students, the challenging of teachers in constructivism classroom. Kew words: cybernetic, constructivism     REFERENCES Atkins, H., Moore, D., and Sharpe, S. 2000. ‘Learning Style Theory and Computer Mediated Communication’. Assicuation of the Advancement of Computing in Education. Available online at Bragg, W.P. 1999. Constructivist learning and Web-based computer conferencing: Qualitative analysis of online interaction among graduate students. Ph.D dissertation. Faifax, VA: George Mason University. Available on line at http://www.csun.edu/sociology/ virexp.htm Accessed on the 3.9.2004 Haythornthwaite, C. 2001. ‘Web-based Education’. Proceedings of the 34th HICSS. IEEE Computer Society Press. Hein, E.G. 1991. Constructivist Learning Theory, International Committee of Museum Educators. Lesley College, Massachusetts USA Lambert, L. et al. 1995. The Constructivist Leader. Teachers College Press. New York. Novak, J. 1998. Learning, Creating and Using Knowledge: Concept maps as tools to understand and facilitate the process in schools and corporations. Lawrence Erlbaum. New Jersey. Norbert Wiener, Cybernetics or Control and Communication in the Animal and the Machine, (Hermann Editions in Paris; Cambridge: MIT Press,Wiley & Sons in NY 1948), Runlee, S. and Daley, B.J. 2002. ‘Constructivist Learning Theory to Web-Based Course Design: an instructional Design Approach’. Australian Journal of Educational Technology. Vol 53(3). Schutte, J.G. (1997). Virtual teaching in higher education: The new intellectual superhighway or just another traffic jam? [verified 2 Nov 2001] http://www.csun.edu/sociology/virexp.htm http://oufcnt5.open.ac.uk/~Hilary_Atkins/emedia.htm Louis Couffignal´s photos & documents (http://histm2.free.fr/H.Couffign.htm)